PENGARUH PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN (PKn) TERHADAP SIKAP NASIONALISME PESERTA DIDIK KELAS VIII DI SMP NEGERI 5 TUALANG KABUPATEN SIAK - Handriani, Loly; Gimin, Gimin; Haryono, Haryono (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The background of this research was the concern of noble values of the nation’s personality that begin to be abandoned by the next generation. The inappropriate attitudes with norms’ life as the result of rapid technological development caused globalization then it is needed the education that can configure the character and attitude to build children of nations’ character more conceive and love their homeland. The formulation of this research was the effect of civic education learning toward students’ nationalism attitude. The number of population this research was 190 students at Eighth Grade of Junior High School 5 Tualang in Kabupaten Siak by using Proportional random sampling the researcher took 98 students as the sample of this research. The technique collecting data used by the researcher were observation, questionnaire, interview, and documentation. To analyze the data the researcher use Simple Linear Regression analysis. Based on the data analysis the researcher conclude that there is significant effect of civic education learning process toward nationalism attitude of Eighth Grade students at Junior High School 5 Tualang in Kabupaten Siak. it was considered from F calculated =19.026 and Ftable=3.94 obtained from distribution list of Fcalculatedwith N= 98 with significant level 5% thus Fcalculated>Ftable (19.026> 3.94 ) in other words, H0 was rejected and Ha was accepted. From the research finding, it showed that there is significant effect of Civic Education learning toward nationalism attitude at Eighth Grade students of Junior High School 5 Tualang in Kabupaten Siak.Keywords: Civic Education learning, Nationalism attitude